ANALISIS PENGARUH PAD, DAU DAN DAK TERHADAP PDRB KABUPATEN/KOTA DI PROVINSI NUSA TENGGARA BARAT - Abdul Mafahir; Aris Soelistiyo (Program Studi Ekonomi Pembangunan, 2017)
The purpose of this study is to determine the effect of District Own Source Revenue, General Allocation Fund and Special Allocation Fund on Gross Regional Domestic Product of Regency / City in West Nusa Tenggara Province. The analytical tool used in this study is by using the District Own Source Revenue, General Allocation Fund, Special Allocation Fund and Gross Domestic Regional Product. This study uses panel data analysis in 10 districts / cities in West Nusa Tenggara Province and also conducted LM test, chow test and haustman test to determine the best regression model. Data obtained from central bureau of statistic (BPS) and directorate-general of regional fiscal balance (DJPK).From result of analysis of panel data of Random Effect Model, it is found that: 1) District own source revenue has an effect that is not significant and negative with probability value 0.131; 2) General Allocation Fund has positive and significant influence with probability value 0.0003; 3) The Special Allocation Fund has no significant positive effect with Probability 0.1600. based on the results of this study then the need for a review of financial management and optimization in the use of the budget so as to create maximum usage.Keywords: District Own Source Revenue, General Allocation Fund and Specific Allocation Fund, Gross Regional Domestic Product.